Trends and levels of the global, regional, and national burden of pulmonary arterial hypertension from 1990 to 2021: findings from the global burden of disease study 2021 - Liu, Le; Li, Chen; Cai, Jing; Kong, Renjing; Wang, Yanjiao; Wang, Yi; Li, Shuang; Zhan, Junkun; Liu, Youshuo (Frontiers in Medicine, 2024)
BackgroundPulmonary arterial hypertension (PAH) is a severe and progressive lung disease that significantly impairs patients’ health and imposes heavy clinical and economic burdens. Currently, there is a lack of comprehensive epidemiological analysis on the global burden and trends of PAH.MethodsWe estimated the prevalence, mortality, disability-adjusted life years (DALYs) of PAH from 1990 to 2021 using the results of the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD). The average annual percentage changes were used to estimate the trends of PAH across 21 regions and 204 countries and territories.ResultsFrom 1990 to 2021, the number of prevalent cases and deaths associated with PAH worldwide increased by 81.5 and 48.4%. However, the age-standardized prevalence rate of PAH remained relatively stable, while the age-standardized mortality rate and DALYs declined. In 2021, the global age-standardized prevalence rate of PAH was 2.28 per 100,000, with 1.78 per 100,000 in males and 2.75 per 100,000 in females. The age-standardized mortality rate of PAH globally was 0.27 per 100,000, and the age-standardized DALYs was 8.24 per 100,000. Among the 21 regions, Western Europe had the highest age-standardized prevalence rate (3.56 per 100,000), while North Africa and the Middle East had the highest age-standardized mortality rate (0.44 per 100,000) and DALYs (14.81 per 100,000). Additionally, older individuals and females are at higher risk of PAH. The age-standardized mortality rate and DALYs associated with PAH increase with age, peaking in the 95+ age group. As the sociodemographic index increased, the age-standardized prevalence rates showed an upward trend, while both the age-standardized mortality rates and DALYs exhibited a downward trend.ConclusionFrom 1990 to 2021, the overall trend of PAH burden presents regional and national variations and differs by age, sex, and sociodemographic index. These findings emphasize the importance of implementing targeted interventions to alleviate the burden of PAH.